TEKNIK PENILAIAN UNJUK KERJA DAN CATATAN ANEKDOT SEBAGAI UPAYA PEMANTAUAN PERKEMBANGAN ANAK DI PAUD AISYIYAH CABANG KARTASURA SUKOHARJO JAWA TENGAH - Purwasih, wahyu (IAIIG Cilacap, 2018)
This study aims to find out how to assess the performance techniques and anecdotal records at PAUD Aisyiyah in Kartasura. The data sources in this study include the principal and class teacher. Data collection is done by observation, interviews, and documentation. Data analysis is done by data reduction, data presentation, and conclusion. Based on the results of the study it can be concluded that the assessment of early childhood education in PAUD Aisyiyah Kartasura has been running in accordance with the 2013 curriculum, namely authentic assessment. This is evidenced by the complete assessment instruments ranging from daily, weekly, monthly, to semester assessments. The teacher is given a blank set of assessments, which will later be filled out by the class teacher and center teacher based on child development. Performance assessment is used to assess all things done by students. While the assessment of anecdotal records contains an assessment of positive children's incidental behavior. After that, the value included in the STPPA assessment recapitulation is a daily diary technique. Whereas compilation of values is a recapitulation of the techniques of anecdotal records, performance, and work.